2017
DOI: 10.1007/s10803-017-3101-9
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver-Teacher Concordance of Challenging Behaviors in Children with Autism Spectrum Disorder Served in Community Mental Health Settings

Abstract: Children with autism spectrum disorder (ASD) exhibit high rates of challenging behaviors that impair functioning and represent the primary presenting problem in mental health (MH) services. Obtaining symptom reports from multiple informants is critical for treatment planning. This study evaluated caregiver-teacher concordance of ratings of the intensity of challenging behaviors in children with ASD receiving MH services, and identified child clinical factors associated with concordance. This sample included 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Previous studies on caregivers and ED patients have reported a larger number of mothers take on this role compared with fathers (Coomber & King, ; Graap et al, ; Jauregui‐Lobera, Ruiz‐Prieto, Bolanos‐Rios, & Garrido‐Casals, ; Macdonald et al, ; Martín et al, ). These results are in line with the current literature highlighting the predominance of female caregivers across mental disorders (Graap et al, ; Roick, Heider, Toumi, & Angermeyer, ; Souza et al, ; Stadnick, Chlebowski, & Brookman‐Frazee, ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies on caregivers and ED patients have reported a larger number of mothers take on this role compared with fathers (Coomber & King, ; Graap et al, ; Jauregui‐Lobera, Ruiz‐Prieto, Bolanos‐Rios, & Garrido‐Casals, ; Macdonald et al, ; Martín et al, ). These results are in line with the current literature highlighting the predominance of female caregivers across mental disorders (Graap et al, ; Roick, Heider, Toumi, & Angermeyer, ; Souza et al, ; Stadnick, Chlebowski, & Brookman‐Frazee, ).…”
Section: Discussionsupporting
confidence: 92%
“…The higher parent ratings regarding ASD symptomatology observed in this study is consistent with several previous studies suggesting that parents tend to rate children's autism symptomatology and challenging behaviors as more impaired (Foley Nicpon et al 2010; Kessler et al 2005; Lopata et al 2016; Murray et al 2009; Posserud et al 2006; Stadnick et al 2017). However, our finding that parents reported higher ratings of adaptive behaviors is inconsistent with prior work (Lane et al 2013; McDonald et al 2016; Szatmari et al 1994; Voelker et al 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Stratis and Lecavalier (2015) highlight the moderating role of child age, cognitive abilities, and diagnosis (intellectual disability versus ASD) in their recent meta-analysis on cross-informant agreement. ASD symptom severity has also been found to moderate parent–teacher concordance, with higher ASD severity associated with greater concordance (Azad et al 2015), although not uniformly (see McDonald et al 2016; Stadnick et al 2017). Although these findings highlight the importance of considering key child characteristics, the majority of this work has focused on ratings of psychopathology and not child adaptive functioning more broadly.…”
Section: Introductionmentioning
confidence: 99%
“…Parents of children with ASD may have a more positive view than their teachers, possibly because teachers can compare the developmental status of many more children of the same age, while parents do not have as many opportunities for comparison. However, in some cases, as we see from the works of Stadnick et al (2017, or Hume et al (2018), a worse evaluation was obtained by the parents, which may be due to different factors, among them parental stress, an aspect which, in spite of its relevance, is Ages 6-10: Parents and teachers of 32 children with ASD (7.47 years) and 21 children without ASD (7.71 years) To analyze the degree of agreement between parents and teachers in the assessment of emotional and behavioral problems and ASD symptoms in students with ASD and their undiagnosed siblings; and to identify predictors of agreement in the assessment of parents and teachers.…”
Section: Discussionmentioning
confidence: 86%
“…In some of the studies reviewed, such as Stadnick et al (2017), the caregivers rated behavior problems, especially externalizing disorders, as more severe than the teachers did when the child had comorbidities with ASD. Along the same lines, , found that teachers rated adaptive skills better than parents rated them; and Hume et al…”
Section: Discussionmentioning
confidence: 99%